2002
DOI: 10.1177/0075424202026002782
|View full text |Cite
|
Sign up to set email alerts
|

Mold Growth on ETICS (EIFS) as a Result of ‘‘Bad Workmanship’’?

Abstract: MOLD GROWTH ON ETICS (EIFS)O N THE EXTERNAL fac¸ades of a housing project, which was completed in autumn, a noticeable biological growth appeared after a short time. As described in [1], especially in the area of the lintels an extended mold infestation could be seen (obvious discolouration). The lintels have not been insulated with expanded polystyrene like the rest of the walls, but with mineral wool. Also mainly circular patterns of the infestation appeared in the middle of the fac¸ades. Drill core samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Previous studies pointed high values of surface moisture content as the cause of biological growth. External surface moisture results from the combined effect of four parameters: surface condensation, wind-driven rain, drying process and properties of the exterior layer (Barberousse et al, 2007; Becker, 2003; Blaich, 1999; Hens and Carmeliet, 2002; Krus et al, 2006; Kunzel and Sedlbauer, 2001; Sedlbauer and Krus, 2002; Venzmer et al, 2008). Although several factors contribute to the phenomenon, surface condensation is a specific hazard for ETICS, due to the low thermal capacity of its external rendering, and has considerable impact on the phenomenon, as it occurs during all the year at equivalent intensity (Barreira and Freitas, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies pointed high values of surface moisture content as the cause of biological growth. External surface moisture results from the combined effect of four parameters: surface condensation, wind-driven rain, drying process and properties of the exterior layer (Barberousse et al, 2007; Becker, 2003; Blaich, 1999; Hens and Carmeliet, 2002; Krus et al, 2006; Kunzel and Sedlbauer, 2001; Sedlbauer and Krus, 2002; Venzmer et al, 2008). Although several factors contribute to the phenomenon, surface condensation is a specific hazard for ETICS, due to the low thermal capacity of its external rendering, and has considerable impact on the phenomenon, as it occurs during all the year at equivalent intensity (Barreira and Freitas, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Drying out of the constructional moisture from the original wall could cause an increase of the moisture content in the structures above the critical level [24][25][26]. It is shown that drying out only by diffusion might take up to eight years [27]. Concerning high WDR for instance in Norway it is concluded that one frequent cause of the defect is the incorrect assembly of the components of the ETICS [28].…”
Section: En-activetics Requirementsmentioning
confidence: 99%
“…Studies already performed in this field pointed high values of surface moisture content as the cause of biological growth. External surface moisture results from the combined effect of four parameters: surface condensation, wind-driven rain, drying process, and properties of the exterior layer [3,5,[7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%